2011
DOI: 10.1161/atvbaha.111.226902
|View full text |Cite
|
Sign up to set email alerts
|

Human Aldose Reductase Expression Accelerates Atherosclerosis in Diabetic Apolipoprotein E−/− Mice

Abstract: Objective There are several pathways that mediate the aberrant metabolism of glucose and that might induce greater vascular damage in the setting of diabetes. The polyol pathway mediated by aldose reductase (AR) has been postulated to be one such pathway. However, it has been reported that AR reduces toxic lipid aldehydes and, under some circumstances, might be anti-atherogenic. Methods and Results Atherosclerosis development was quantified in two lines of transgenic mice expressing human AR (hAR) crossed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 35 publications
2
57
0
Order By: Relevance
“…Moreover, AR inhibition resulted in reduction of oxLDL-induced intracellular oxidative stress; oxLDL-induced upregulation of AR in human macrophages was observed to be proinflammatory in foam cells and may be a potential link between the clinical sequelae associated with hyperlipidemia, atherosclerosis, and diabetes mellitus [76]. Recently, atherosclerosis development was quantified in transgenic mice expressing human AR (hAR) double crossed with the apoE knockout; the transgenes were used to increase the normally low levels of this enzyme in wild-type mice [77]. This study demonstrated that hAR expression in apoE null mice is atherogenic and that expression specifically in endothelial cells also leads to a significant disease progression.…”
Section: Endotoxin-induced Inflammationmentioning
confidence: 99%
“…Moreover, AR inhibition resulted in reduction of oxLDL-induced intracellular oxidative stress; oxLDL-induced upregulation of AR in human macrophages was observed to be proinflammatory in foam cells and may be a potential link between the clinical sequelae associated with hyperlipidemia, atherosclerosis, and diabetes mellitus [76]. Recently, atherosclerosis development was quantified in transgenic mice expressing human AR (hAR) double crossed with the apoE knockout; the transgenes were used to increase the normally low levels of this enzyme in wild-type mice [77]. This study demonstrated that hAR expression in apoE null mice is atherogenic and that expression specifically in endothelial cells also leads to a significant disease progression.…”
Section: Endotoxin-induced Inflammationmentioning
confidence: 99%
“…4 The overexpressed AR in blood causes sorbitol accumulation and the reduction of NADPH in cells by activating the polyol pathway, which results in cell damage and induces the occurrence of chronic diabetic complications. Vedantham et al 31 utilized immunofluorescence and Western blotting to detect the expression of AR in the aortic arch of mice, carotid artery specimens from humans, and AR + murine aortic endothelial cells. To explore the treatment of diabetes against AR, we constructed eukaryotic expression vectors containing the human AR gene and the subsequently developed cell model can be used for aldose reductase inhibitor (ARI) screening.…”
Section: Discussionmentioning
confidence: 99%
“…Sorbitol is subsequently converted into fructose and thereafter into the highly reactive 3-deoxyglucosone, which promotes the formation of AGEs (Kashiwagi et al, 1994;Schalkwijk et al, 2004;Oyama et al, 2006;Giacco and Brownlee, 2010;Sena et al, 2012;Yoshida et al, 2012;Mapanga and Essop, 2016). Overexpression of an AR transgene in ECs of diabetic mice accelerates atherosclerosis and inhibition of endothelial AR reduces ROS production and EC proliferation (Obrosova et al, 2003;Tammali et al, 2011;Vedantham et al, 2011;Yadav et al, 2012).…”
Section: A Diabetes Mellitusmentioning
confidence: 99%